An Assessment of Polar Solvent Extraction on Free Scavenging Activity of Sonneratia caseolaris - Iranawati, Feni; Oktavia, Yoan; Kasitowati, Rarasrumdyah; Kartikaningsih, Hartati; Harlyan, Ledhyane Ika; Arifin, Sunanto (The Journal of Experimental Life Science, 2024)
Degenerative diseases such as stroke and cancer arise due to oxidative stress by a large number of reactive oxygen species (ROS) in the body. Free radical scavenging (antioxidant) compounds are needed to neutralize the ROS. The natural antioxidant potential of mangrove species Sonneratia caseolaris has been widely explored. However, its extraction is usually carried out with polar solvents such as methanol. Besides being more toxic than ethanol, methanol can cause blindness and death when inhaled in large quantities. Additionally, Indonesia, as the country with the largest Muslim population, requires the use of halal products for food and cosmetics. This study aims to analyze the scavenging activities of S. caseolaris with methanol and distilled water as the polar solvents for extraction. Antioxidant activity was tested with the free radical assay method of DPPH (2,2-diphenyl-1-picrylhydrazyl radicals). The test results were calculated as the IC50 value, a concentration capable of reducing free radicals by 50%. The antioxidant activity test showed that the IC50 values of methanol and distilled water were 18.9 ppm and 36 ppm, respectively. Therefore, both are considered very strong antioxidants. It indicates that distilled water is an acceptable substitute for methanol in the extraction process. Keywords: antioxidant, extraction, mangrove, solvent, Sonneratia.